The Wiley handbook of obsessive compulsive disorders - Abramowitz, Jonathan S.; McKay, Dean 1966-; Storch, Eric A. (Wiley Blackwell, 2017)
The Wiley Handbook of Obsessive Compulsive Disorders, 2 volume set, provides a comprehensive reference on the phenomenology, epidemiology, assessment, and treatment of OCD and OCD-related conditions throughout the lifespan and across cultures.